THE DISTRIBUTION OF GLOMEROMYCOTA IN CACAO RHIZOSPHERE IN INDONESIA - Kartini - Kramadibrata (REINWARDTIA, 2009)
KRAMADIBRATA, K. 2009. The distribution of Glomeromycota in cacao rhizosphere in Indonesia. Reinwardtia 12(5): 347–356. A study on the distribution of Glomeromycota (AF) in cacao soils in several cacao plantations in Java and Bali showed that Acaulospora walkeri as a dominant species and A. scrobiculata as a predominant species.